Intersegmental coordination differences between beginning performers executing a badminton smash for accuracy or velocity - Strohmeyer, D.; Armstrong, C.; Litvinsky, Y.; Nooney, R.; Moore, J.; Smith, K. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Proper coordination is generally accepted as a very important process in skilful execution of many movement activities. It is also believed ballistic skills will exhibit a sequential intersegmental coordination pattern. Yet, what we know about how intersegmental coordination develops is relatively minimal. The purpose of this investigation was to examine a new skill (badminton smash) under two conditions (accuracy and velocity) to determine which condition would elicit the most theoretically correct intersegmental coordination pattern.